2022
DOI: 10.3390/polym14102076
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Properties of CFRP Composite Laminates Containing Spread-Tow Thin-Plies

Abstract: With the development of spread-tow, thin-ply technology, ultra-thin composite laminates could be produced. Composite bolted joints are commonly used on aircraft’s load-bearing structures and are considered the main cause of stress concentration. The aim of this research is to investigate the bolted joint behavior of composite laminates that combine thin-plies and conventional thick-plies in a predetermined stacking sequence. The impact of thin-ply placement within the stack on bearing strength, including the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 18 They established an experimental setup for ultrasonic-guided wave-based damage detection using piezoelectric sensors and processed the response signals using Hilbert transform (HT), Fourier transform (FFT), and wavelet transform (CWT) techniques. 19 Hassan and Tamer 20 explored how composite laminates with a specific arrangement of thin and thick plies in a predetermined sequence behave when used in bolted joint.…”
Section: Composite Materials In Engineering Structuresmentioning
confidence: 99%
“… 18 They established an experimental setup for ultrasonic-guided wave-based damage detection using piezoelectric sensors and processed the response signals using Hilbert transform (HT), Fourier transform (FFT), and wavelet transform (CWT) techniques. 19 Hassan and Tamer 20 explored how composite laminates with a specific arrangement of thin and thick plies in a predetermined sequence behave when used in bolted joint.…”
Section: Composite Materials In Engineering Structuresmentioning
confidence: 99%
“…Dong-Uk Kim et al and D. Sivakumar et al examined the mechanical bearing strength and failure mechanisms of composite-to-metal joining structures connected by mechanically secured joints, demonstrating composites’ potential as a replacement for steel in ships and offshore constructions [ 43 , 44 ]. Furthermore, Hassan Al-shahrani et al, Z. Sajid et al, Anyang Wang et al, Jing-chao Wei et al, Junshan Hu et al, Andrew N. Dickson et al, Isha Paliwal et al, and Liyuan Qu et al have made significant contributions to our understanding of bolted joint behavior in composite materials, providing valuable insights for the development of innovative products and technologies [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dong-Uk Kim et al and D. Sivakumar et al examined the mechanical bearing strength and failure mechanisms of composite-to-metal joining structures connected by mechanically secured joints, demonstrating composites' potential as a replacement for steel in ships and offshore constructions [43,44] [45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Mamalis et al examined the crushing characteristics of thin‐walled square CFRP tubes under static and dynamic axial compressive loads 13 . It was concluded that the crushing behavior of CFRP structures is typically determined by the development of fracture, inter‐ply delamination, and extensive micro‐cracking, which depends on the structural and material features, such as fiber orientation, the number of layers, the characteristics of each individual layer, and so on 14 . Due to these interacting factors, designing CFRP energy‐absorbing structures is substantially complex and difficult than designing conventional metallic structures.…”
Section: Introductionmentioning
confidence: 99%
“…13 It was concluded that the crushing behavior of CFRP structures is typically determined by the development of fracture, inter-ply delamination, and extensive microcracking, which depends on the structural and material features, such as fiber orientation, the number of layers, the characteristics of each individual layer, and so on. 14 Due to these interacting factors, designing CFRP energy-absorbing structures is substantially complex and difficult than designing conventional metallic structures. Experimental studies on the impact of fiber orientation on the energy absorption properties of composite tubes subjected to axial loading were undertaken by Mahdi et al 15,16 For improving the load-carrying capability and energy absorption, they demonstrated the benefits of placing fiber orientations of 15 /75 and 75 /15 .…”
Section: Introductionmentioning
confidence: 99%